The Influence of Outpatient Pharmacy Service Quality on Patient Satisfaction at Hermina Bekasi Hospital - Fauzobihi, Fauzobihi; Sutiyasih, Hety; Junengsih, Junengsih (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Patient satisfaction is the level of patient feelings that arise due to the performance of health services obtained after comparing the patient with what he feels. This research was conducted at the Hermina Bekasi Hospital because at this institution no research had been conducted on the quality of pharmaceutical services on outpatient satisfaction. The research method used is quantitative with an associative method to determine the relationship between service quality variables and patient satisfaction variables. Based on the results of the analysis carried out using SPSS 21.0, the value of the influence of Service Quality (X) on Patient Satisfaction (Y) can be narrated using the regression formula Y= a+bX, so the regression value resulting from the calculation above is Y = 16,725 + 0.721X. The constant value (a) is = 16,725 while the coefficient value (b) = 0.721. The meaning of this equation is that if there is no quality of service, then patient satisfaction will be worth 16,725 units. However, if there is an increase of one unit/unit of the service quality variable, it will affect the increase in patient satisfaction by 0.721. Based on the calculations obtained, tcount is 13.092 > t table 1.984, it can be concluded that is rejected and is accepted because t count is greater than t table. Thus it can be concluded that there is an influence of Service Quality on Patient Satisfaction.